Present and future drug treatment for Parkinson's disease - Schapira, A (BMJ Group, 2005)
Considerable advances made in defining the aetiology, pathogenesis, and pathology of Parkinson's disease (PD) have resulted in the development and rapid expansion of the pharmacopoeia available for treatment. Anticholinergics were used before the introduction of levodopa which is now the drug most commonly used. Dopamine agonists are effective when used alone or as an adjunct to levodopa, while monoamine oxidase B inhibitors improve motor function in early and advanced PD. However, treatment mainly addresses the dopaminergic features of the disease and leaves its progressive course unaffected; the drug treatment available for the management of non-motor symptoms is limited. This article seeks to set current treatment options in context, review emerging and novel drug treatments for PD, and assess the prospects for disease modification. Surgical therapies are not considered.